สุขภาพจิตและปัจจัยที่เกี่ยวข้องของพยาบาลห้องผ่าตัดโรงพยาบาลของรัฐแห่งหนึ่งในกรุงเทพมหานคร - ชุติกาญจน์ มณีผ่อง (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This research was a cross-sectional study with the objectives to study the mental health and related factors of perioperative nurses at a public hospital in Bangkok. The samples were 124 nurses. Instruments used in collecting datas were divided into four parts: demographic data, job characteristics questionnaire, Maudsley Personality Inventory (MPI) and Thai Mental Health Indicator (TMHI-66). The datas were analyzed by SPSS program such as percentage, means, standard deviation, chi-square test, t-test, Pearson’s coefficient of correlation, and comparison test by LSD and Stepwise Multiple regression analysis. The study found that 47.6% of perioperative nurse had mental health in fair level, 28.2% was in good level and 24.2% was in poor level. E-Scale (Extraversion-Introversion) and N-scale (Neuroticism and Stability) were negatively correlated to the mental health with statistically significant (p<0.05), Relationship among colleagues and job environment were positively correlated to mental health with p<0.05. In conclusion, Neuroticism and job environment were significantly factors in prediction of mental health.